Analysis of Factors Affecting Disclosure of Islamic Social Reporting (ISR): Analisis Faktor-Faktor yang Mempengaruhi Pengungkapan Islamic Social Reporting (ISR) - Daniyati, Adila Inas; Hariyanto, Wiwit (Universitas Muhammadiyah Sidoarjo, 2018)
This.study aims to.determine.the effect of Company Size (Return), Return On Assets (ROA), Debt to EquityRatio (DER) on the disclosure of Islamic Social Reporting (ISR) partially and simultaneously on companies recorded in the JII (Jakarta Islamic Index) period 2015-2017 with 19 companies.This study uses a quantitative approach. By using secondary data where data collection is on the IDX of the Faculty of Economics and Business, University of Muhammadiyah Sidoarjo or from the official website of the IDX. Data collection is done by tracing financial reports, annual reports and ongoing.reports or company social information selected as samples. The results of this study state that partially the company size variable (size), and Return on Assets (ROA) have a significant effect on ISR disclosure while the Debt to Equity Ratio (DER) variable does not significantly influenceISR disclosure. Simultaneously the company size variable (size), return on assets (ROA) and Debt to Equity Ratio (DER) affect the ISR disclosure.